Aerobic Training–Induced Gut Microbiome Shifts And Associations With Insulin Sensitivity In Prediabetes - Dr. Arupjyoti Kakati, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Prediabetes is characterized by impaired glucose regulation and represents a critical window for preventive strategies. Emerging evidence links gut microbiome composition to metabolic health and insulin sensitivity. Exercise, particularly aerobic training, has been shown to modify gut microbial diversity and function, but its effects in individuals with prediabetes remain poorly defined. Methods: We conducted a 16-week randomized controlled trial involving 92 adults with prediabetes (age 40–65 years, BMI 27–35 kg/m²). Participants were randomized to an aerobic training group (n=46; supervised treadmill and cycling sessions, 45 minutes, 4 days/week, at 60–70% VO₂max) or a control group (n=46; standard lifestyle advice). Gut microbiome profiles were analyzed using 16S rRNA sequencing of stool samples at baseline and week 16. Insulin sensitivity was assessed by homeostatic model assessment of insulin resistance (HOMA-IR) and oral glucose tolerance test (OGTT). Statistical analyses included paired t-tests, PERMANOVA for microbial community structure, and multivariable regression models. Results: Aerobic training significantly reduced HOMA-IR (−22%, p<0.01) and improved 2-h OGTT glucose levels compared with controls (−18%, p<0.05). Training increased microbial α-diversity (Shannon index +15%, p<0.01) and shifted β-diversity toward greater abundance of butyrate-producing taxa (Faecalibacterium prausnitzii, Roseburia spp.). Reductions in pro-inflammatory taxa (Enterobacteriaceae) were observed. Multivariable regression demonstrated that increases in Faecalibacterium abundance independently predicted improvements in HOMA-IR (β = −0.35, p=0.002). Conclusion: Aerobic training in prediabetic adults induces beneficial gut microbiome shifts characterized by enrichment of short-chain fatty acid–producing taxa, alongside improvements in insulin sensitivity. These findings highlight exercise as a modifiable intervention targeting host–microbe interactions in metabolic disease prevention.